ENHANCING EFL STUDENTS’ SPEAKING FLUENCY THROUGH TASK-BASED LANGUAGE TEACHING WITH FOREIGN TOURISTS IN YOGYAKARTA - Surahman, Dede; Ma’sum, Iin Inayah (ENGLISH, 2025)
This study explores the implementation of Task-Based Language Teaching (TBLT) in authentic field interactions between Indonesian university students and a foreign tourist in Yogyakarta. The research aimed to explore (1) students’ perceptions of TBLT activities, (2) the effectiveness of task-based interaction in enhancing speaking fluency, and (3) tourist’s responses to Yogyakarta’s cultural diversity. Participants consisted of two undergraduate students from the English Language Education Department and one foreign tourist visiting Yogyakarta. The present study used a qualitative case study where the data were collected through field interviews, direct lecturer observation, video documentation, and student reflection journals, and analyzed using methodological and source triangulation. Findings show that students perceived TBLT as challenging but beneficial, enabling them to apply classroom theory into real communicative practice while building confidence. The activities proved effective in developing fluency, as students were able to sustain natural interaction, employ communication strategies, and reflect positively on their progress. The tourist responded warmly, emphasizing Yogyakarta’s cultural richness, culinary heritage, and hospitality, which fostered intercultural dialogue. The study concludes that TBLT not only promotes linguistic gains but also enhances intercultural competence, with students acting as cultural ambassadors in authentic encounters. Future research is recommended to involve a larger participant base and diverse tourist sites to broaden the scope of findings.